The Effect of Slickwater on Shale Properties and Main Influencing Factors in Hydraulic Fracturing - Jiawei Liu; Xuefeng Yang; Shengxian Zhao; Yue Yang; Shan Huang; Lieyan Cao; Jiajun Li; Jian Zhang (Geofluids)
As shale gas reservoirs have low porosity and low permeability, hydraulic fracturing is a necessary means for industrial exploitation of shale gas. In this study, aiming at the problem of reservoir damage in the process of hydraulic fracturing of shale gas reservoir, a physical simulation method of slickwater fracturing fluid flow in shale core has been established. The change laws of physical parameters of the shale were quantified after slickwater fracturing fluid filtrating into it. The main factors affecting physical parameters of shale matrix around fractures were found out in the process of fracturing, shut-in, and flowback of slickwater fracturing fluid. The results show that after treated by slickwater fracturing fluid, the wettability of shale becomes more uniform in distribution (the water contact angles from 43° to 48°). In the fracturing filtration zone, the damage rate of fracturing fluid to shale porosity is 6.4%-42.0%. Low differential pressure flowback can reduce the damage of the shale, and prolonging the time of shut-in has no obvious effect on the damage to porosity. After 0.3 d (imbibition stability time), the damage of fracturing fluid to shale permeability is basically stable (55.9%). Permeability damage is mainly caused by residue of the fracturing fluid in large pores and bound water in small pores. Analysis of weights of all fracturing parameters shows that flowback differential pressure has the largest influence weight on shale porosity (51.4%), and well shut-in time has the largest influence weight on shale permeability (62.7%). Therefore, in the production process, it is suggested to properly reduce the backflow differential pressure and moderately shorten the well shut-in time.